Pengenalan Artificial Intelligence untuk Pengembangan Minat dan Bakat Siswa SMA Negeri 11 Bulukumba - Andi Baso Kaswar; Dyah Darma Andayani; Gufran Darma Dirawan; Ayu Tri Wardani; Asmaul Husnah Nasrullah (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2024)
Artificial intelligence (AI) is a branch of computer science aimed at creating machines capable of performing tasks that usually require human intelligence. Currently, artificial intelligence technology is widely applied in various lives because of its effectiveness and efficiency from various points of view. Given the importance and threat of artificial intelligence in today's life, various forms of training have been held to introduce artificial intelligence to the public. Various artificial intelligence training activities show that an understanding of artificial intelligence is needed today. Therefore, it is important to broaden the horizons and knowledge of this field to interact and compete in the future. The same thing was felt by teachers and students of SMA Negeri 11 Bulukumba as partners in this community service activity. There is a desire for partners to understand the field of artificial intelligence in order to develop students' interests and talents. However, SMA Negeri 11 Bulukumba experiences obstacles in understanding more deeply related to artificial intelligence due to limited access and human resources who understand the field. Therefore, in this community service activity, an introduction to artificial intelligence was carried out to develop the interests and talents of SMA Negeri 11 Bulukumba students. The implementation of this training was divided into three main stages: preparation, implementation, and evaluation. With this training, the knowledge and insights of SMA Negeri 11 Bulukumba students are increasingly broadened with regard to developing interest and talent in the field of artificial intelligence.